Remote boundary-scan testing through micro-webservers - José Martins Ferreira (2009)
The IEEE 1149.1 standard test access port and boundary-scan architecture [1] was approved in 1990 in response to the need for coping with shrinking sizes due to advanced packaging and mounting technologies, and also with the increasing complexity of modern microelectronic devices. Boundary-scan test (BST) was quickly adopted by all industry sectors, including test equipment manufacturers, CAD tool providers, and microcircuit designers and manufacturers. Many tools and integrated solutions are now available on the market to support BST, but they are essentially dedicated to production test environments. The work presented in this document addresses the development of a network of low-cost distributed BST controllers, based on micro-webserver boards.